Relationship between advertising disclosure, influencer credibility and purchase intention - Vesna Sesar; Ivana Martinčević; Monika Boguszewicz-Kreft (Journal of Risk and Financial Management, 2022)
Understanding influencer credibility and online advertising and explaining its implications is the basis for analyzing customer purchase behavior. Novelties in digital marketing are visible in the growth of advertising through digital platforms using micro-influencers, compared to the former trend of using celebrities in creating brand awareness with the purpose to reach many customers and influence their buying decisions. The aim of this study is to examine how advertising disclosure (displayed/not displayed) affects influencer credibility, while analyzing influencer type (celebrity/micro-influencer) as a moderator variable underlying this relationship. Further, this paper investigates whether brand awareness mediates the relationship between influencer credibility and purchase intention. The questionnaire was designed and data were collected from 364 respondents using the convenience sampling method on the student population from one Croatian university. Regression analysis was performed to test the set hypothesis in SPSS using the PROCESS approach and independent sample t-test. The findings show: (1) displayed advertising status increases influencers' credibility, and (2) this relationship is not moderated by influencer type. Moreover, (3) influencer credibility has a positive and significant relationship with purchase intention, and (4) this relationship is mediated through brand awareness. Research results indicate the importance of advertising disclosure and influencer credibility in influencer marketing, since brand awareness created through influencers' credibility increased by displayed advertising disclosure significantly affects purchase intention of participants.
Keywords: 650; advertising disclosure; brand awareness; influencer marketing; mediation model; moderation model; purchase intention